The large-scale impact of anthropogenic mixing by offshore wind turbine foundations in the shallow North Sea - Christiansen, Nils; Carpenter, Jeffrey R.; Daewel, Ute; Suzuki, Nobuhiro; Schrum, Corinna (Frontiers in Marine Science, 2023)
Structure drag from offshore wind turbines and its physical impacts on the marine environment of the German Bight are investigated in this study. The flow past vertical cylinders, such as wind turbine foundations, and associated turbulent mixing has long been studied, but questions remain about anticipated regional implications of offshore wind infrastructure on physical and biogeochemical conditions. Here, we present two existing modeling approaches for simulating wind turbine foundation effects in regional ocean models and discuss the problematic use of very high resolution in hydrostatic modeling. By implementing a low-resolution structure drag parameterization in an unstructured-grid model, we demonstrate the impacts of monopile drag on hydrodynamic conditions, validated against recent in-situ measurements. Although the anthropogenic mixing is confined at wind farm sites, our simulations show that structure-induced mixing affects much larger, regional scales. The additional turbulence production emerges as the driving mechanism behind the monopile impacts, leading to changes in both the current velocities and stratification, with magnitudes of about 10 %, similar in magnitude to regional annual and interannual variability. This study provides new insights into the hydrodynamic impact of offshore wind farms at their current development levels and emphasizes the need for further research in view of potential restructuring of the future coastal environment.